2019
DOI: 10.1111/jvim.15522
|View full text |Cite
|
Sign up to set email alerts
|

Usage patterns of carbapenem antimicrobials in dogs and cats at a veterinary tertiary care hospital

Abstract: Background Carbapenems are a class of antimicrobials reserved for resistant infections or systemically ill people, yet the extent and context in which they are prescribed in the small animals is understudied. Hypothesis/Objective To describe cases in dogs and cats treated with carbapenems to establish baseline data regarding the types of infections, outcomes, and resistance profiles of target infections. We hypothesize that prescribing practices for carbapenems at a vet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 24 publications
(46 reference statements)
1
31
0
2
Order By: Relevance
“…A recent retrospective study describing the usage of carbapenem in a similar institution demonstrated a similar low prescription rate. However, de-escalation to a lower tier antimicrobial or no antimicrobial was rarely performed in that study (59). The WHO has classified carbapenems on the "Watch" group of antimicrobials (60), which overlaps with the highest priority agents on the list of critically important antimicrobial drugs for human medicine.…”
Section: Discussionmentioning
confidence: 99%
“…A recent retrospective study describing the usage of carbapenem in a similar institution demonstrated a similar low prescription rate. However, de-escalation to a lower tier antimicrobial or no antimicrobial was rarely performed in that study (59). The WHO has classified carbapenems on the "Watch" group of antimicrobials (60), which overlaps with the highest priority agents on the list of critically important antimicrobial drugs for human medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Another significant finding in this study is, to our knowledge the first isolation of a CTX-M-15 and NDM-1, together with OXA 1, TEM producing Enterobacter cloacae ST114 from a vaginal swab of a dog from Serbia (strain ESBL40). Carbapenems-resistance in bacteria of animal origin is a subject of great concern due to their importance in therapy of life-threatening infections in human and in veterinary medicine [26,43,46]. Although several publications state that the risk of carbapenem resistance in animals is low due to the limited use of this class in veterinary medicine [26,43,46], this is the second report on the detection of carbapenemases carrying bacteria associated with canine UGI from Serbia [36] and bla NDM , bla VIM , bla IMP , bla OXA and bla KPC carbapenemases have been detected worldwide in companion animals.…”
Section: Discussionmentioning
confidence: 99%
“…Carbapenems-resistance in bacteria of animal origin is a subject of great concern due to their importance in therapy of life-threatening infections in human and in veterinary medicine [26,43,46]. Although several publications state that the risk of carbapenem resistance in animals is low due to the limited use of this class in veterinary medicine [26,43,46], this is the second report on the detection of carbapenemases carrying bacteria associated with canine UGI from Serbia [36] and bla NDM , bla VIM , bla IMP , bla OXA and bla KPC carbapenemases have been detected worldwide in companion animals. Unlike carbapenemases, CTX-M-15 is highly prevalent in Enterobacter cloacae and CTX-M-15-producing ST114 Enterobacter cloacae has been recently reported as a high-risk clone for public health which was predominant in cats, dogs and horses [47,48].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations